Vitamin D Regulates the Microbiota to Control the Numbers of RORγt/FoxP3+ Regulatory T Cells in the Colon - Cantorna, Margherita T.; Lin, Yang-Ding; Arora, Juhi; Bora, Stephanie; Tian, Yuan; Nichols, Robert G.; Patterson, Andrew D. (Frontiers in Immunology, 2019)
The active form of vitamin D (1,25(OH)2D) suppresses experimental models of inflammatory bowel disease in part by regulating the microbiota. In this study, the role of vitamin D in the regulation of microbe induced RORgt/FoxP3+ T regulatory (reg) cells in the colon was determined. Vitamin D sufficient (D+) mice had significantly higher frequencies of FoxP3+ and RORgt/FoxP3+ T reg cells in the colon compared to vitamin D deficient (D-) mice. The higher frequency of RORgt/FoxP3+ T reg cells in D+ colon correlated with higher numbers of bacteria from the Clostridium XIVa and Bacteroides in D+ compared to D- cecum. D- mice with fewer RORgt/FoxP3+ T reg cells were significantly more susceptible to colitis than D+ mice. Transfer of the cecal bacteria from D+ or D- mice to germfree recipients phenocopied the higher numbers of RORgt/FoxP3+ cells and reduced susceptibility to colitis in D+ versus D- recipient mice. 1,25(OH)2D treatment of the D- mice beginning at 3 weeks of age did not completely recover RORgt/FoxP3+ T reg cells or the Bacteriodes, Bacteriodes thetaiotaomicron, and Clostridium XIVa numbers to D+ values. Early vitamin D status shapes the microbiota to optimize the population of colonic RORgt/FoxP3+ T reg cells important for resistance to colitis.